AN ANALYSIS OF METAPHOR AND SIMILE TRANSLATION STRATEGIES IN “THE JUNGLE BOOK” NOVEL - Harun Sigit; Silvia Erlin Aditya Sembiring (Literary Criticism, 2020)
This study examined about metaphor and simile translation strategies in “The Jungle Book" novel. The objective of the study are: (1) To find out the metaphor and simile in “The Jungle Book” Novel (2) To know the translation strategies used by the translator in translating. The method of this study is descriptive qualitative. It is concerned with the description of the data in the form of conversation and naration. In analyzed the data, the writer used technique developed by Spradley and Newmark theories. The result of study indicate that most dominanat is found more than simile in “The Jungle Book” novel. While the translation strategies used by the translator in translatig in “The Jungle Book” novel are most dominant metaphor namely reproducing the same metaphorical image in the targer language and simile found is Literal translation (retention of the same vehicle/image). Keywords : Metaphor, Novel, Simile, Strategies Translation, The Jungle Book